Impact of Community Stress on Community Empowerment Processes in Preventing Daily Emergency in Volcanic Area - Rahariyani, Loetfia Dwi; Fadilah, Nikmatul; Badi'ah, Atik (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Volcanic disasters have a psychological impact on society. Community stress must be anticipated and overcome as soon as possible so as not to cause greater losses. Community empowerment based on the experience of dealing with and dealing with disasters, managing risks, reducing, and recovering from disasters is an adaptive community coping. The purpose was to determine the effect of community stress on the community empowerment process in preventing daily emergencies in the volcanic disaster area. This study used an analytic design through a cross-sectional approach. A sample of 165 people in Hargobinangun Village, Pakem District, Sleman Regency, Yogyakarta, Indonesia, was taken using purposive sampling. The sample criteria were adults who live in the village and can read and write. Community stress and community empowerment were taken using a questionnaire from July until August 2020. Data analysis used T-test. Most communities have low stress for the threat of disaster but have high stress for attachment to the region. Community stress influence on community empowerment process (p-value 0.027). Community stress will affect the degree of reaction and have an impact on the community empowerment process in preventing daily emergencies. Further research is recommended to identify specific factors that cause stress in communities in volcano disaster areas.